No classical (anti-)de Sitter solutions with O8-planes - Cribiori, Niccolò; Junghans, Daniel (Physics letters, 2019)
It was recently proposed that type IIA string theory may allow classical de Sitter solutions with O8-planes as the only localized sources. We show tha…
Available online 18 April 2019
Gesehen am 07.08.2019